Fabrication of ssDNA/Oligo(ethylene glycol) monolayers and complex nanostructures by an irradiation-promoted exchange reaction - Khan Hira, Md. Nuruzzaman; Tjong, Vinalia; Zharnikov, Michael (Angewandte Chemie. International edition, 2012)
Creative design: An approach to preparing mixed monolayers of thiolated single-stranded DNA (ssDNA) and oligo(ethylene glycol)s (OEG-AT) in a broad range of compositions as well as ssDNA/OEG-AT patterns of any required shape (see top figure) has been shown. A combination of this approach with surface-initiated enzymatic polymerization allows complex 3D DNA nanostructures to be sculpted with high spatial precision (bottom).